Plasma cytokine levels imbalance in cirrhotic patients with impaired glucose tolerance and diabetes mellitus: a prospective study - García Compeán, Diego; Jáquez Quintana, Joel Omar; Lavalle González, Fernando Javier; González González, José Alberto; Maldonado Garza, Héctor Jesús; Villarreal Pérez, Jesús Zacarías (2014)
Aims. To define if there is an imbalance in plasma levels of proinflammatory, fibrogenic and antifibrogenic cytokines in patients with liver cirrhosis (LC) and impaired glucose tolerance (IGT) or diabetes mellitus (DM). Material and methods. We randomly selected 54 out of 100 patients with LC who had normal fasting plasma glucose (FPG) levels. Three groups were formed based on an oral glucose tolerance test (OGTT) results: 18 patients were normal, 18 had IGT, and 18 had DM. Plasma levels of cytokines were measured: TNFD, soluble tumor necrosis factor receptor 1 (sTNF-R1), leptin, TGF-E1, and hepatocyte growth factor (HGF). Also, fasting plasma insulin (FPI) levels were determined and HOMA2-IR was calculated. Results were compared with those of a control group of 18 patients without liver disease nor DM. Intergroup comparison was performed using non parametric tests. Results. Significantly higher sTNF-R1 and lower TGF-E1 were found in patients with IGT and DM compared to controls. Leptin, HGF, and TNF-D levels showed no significant differences. According to Child Pugh classification all cytokines levels were impaired in groups B or C as compared to group A. Positive correlations between sTNF-R1 and HOMA2-IR and between leptin and HOMA2-IR were found. Conclusions. IGT and DM were associated with abnormalities of sTNF-R1 and TGF-E1 compared to non cirrhotic controls. Among cirrhotic patients impairment of all cytokines were more marked in advanced liver disease. Finally, sTNF-R1and leptin correlated with IR. These findings suggest that IGT and DM may be causally implicated with liver inflammation process.